2019
DOI: 10.1017/ice.2019.88
|View full text |Cite
|
Sign up to set email alerts
|

Oral vancomycin prophylaxis during systemic antibiotic exposure to preventClostridiodes difficileinfection relapses

Abstract: Objective:To determine whether oral vancomycin prophylaxis accompanying systemic antibiotics reduces the risk of relapse in patients with history of Clostridioides difficile infection (CDI).Design:Retrospective cohort study.Patients:Adult inpatients with a history of CDI who received systemic antibiotics in either of 2 hospitals between January 2009 and June 2015.Methods:We compared relapse rates in patients who started oral vancomycin concurrently with systemic antibiotics (exposed group) versus those who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…26,27 Despite clear differences between the populations included in the studies, 7 of 9 studies found OVP use to be associated with lower CDI. Splinter et al 23 and Caroff et al 22 found this reduction to be statistically insignificant. However, the first study was underpowered, including only 29 patients, while in the latter the mean duration of OVP treatment was 2.29 days, which might have been insufficient exposure.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…26,27 Despite clear differences between the populations included in the studies, 7 of 9 studies found OVP use to be associated with lower CDI. Splinter et al 23 and Caroff et al 22 found this reduction to be statistically insignificant. However, the first study was underpowered, including only 29 patients, while in the latter the mean duration of OVP treatment was 2.29 days, which might have been insufficient exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, there is no current consensus on the dose of OVP, duration of treatment or long-term outcomes. In this review, we evaluated 8 studies that examined patients with different risk factors for CDI, including previous CDI followed by systemic antibiotic therapy, 19,22,28,29 immunosuppression due to solid organ transplant, 23 or hematopoietic cell transplant, 24,25 and elderly patients. 26,27 Despite clear differences between the populations included in the studies, 7 of 9 studies found OVP use to be associated with lower CDI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Despite the lack of robust supporting evidence, secondary prophylaxis with oral vancomycin in patients on systemic antibiotics for infections other than CDI has become common practice. [2][3][4] We read "Oral vancomycin prophylaxis (OVP) during systemic antibiotic exposure to prevent Clostridioides difficile infection relapses" by Caroff et al 4 with great interest. The authors reported that OVP was effective in reducing CDI relapse in patients with incident CDI (1 previous CDI) but not recurrent CDI (≥2 CDI episodes).…”
mentioning
confidence: 99%